Noisy Light Augments the Na+ Current in Somatosensory Pyramidal Neurons of Optogenetic Transgenic Mice - Mabil, Pedro; Huidobro, Nayeli; Torres-Ramirez, Oswaldo; Flores-Hernandez, Jorge; Flores, Amira; Gutierrez, Ranier; Manjarrez, Elias (Frontiers in Neuroscience, 2020)
In previous reports, we developed a method to apply Brownian optogenetic noise-photostimulation (BONP) up to 0.67 mW on the barrel cortex of in vivo ChR2 transgenic mice. In such studies, we found that the BONP produces an increase in the evoked field potentials and the firing frequency response of pyramidal neurons to somatosensory mechanical stimulation. Here we extended such findings by examining whether the same type of BONP augments the Na+ current amplitude elicited by voltage-clamp ramps of isolated pyramidal neurons from the somatosensory cortex of ChR2 transgenic mice and wild type mice. In all neurons from the ChR2 transgenic mice, but not from the wild type mice, we found that the peak amplitude of a TTX-sensitive Na+ current and its inverse of latency exhibit inverted U-like graphs as a function of the BONP level. It means that an intermediate level of BONP increases both the peak amplitude of the Na+ current and its inverse of latency. Our research suggests that the impact of BONP on the Na+ channels of pyramidal neurons could be associated with the observed augmentation-effects in our previous in vivo preparation. Moreover, it provides information for an appropriate range of light intensity, less than 0.67 mW, which could avoid opto-non-genetic responses due to temperature changes.